O cotidiano e as formas da socialidade: a comunidade virtual web novelas fake - Oliveira, Siméia Rêgo de (2014)
The current research intends to take a look at the impact of the social interactions made by the intermediation of the computer thru the virtual community called, Web Novels Fake on Orkut. This work also investigated the reasons for individuals to interact as fake profile in such a social network. The proposal of such dissertation intends to contribute to the study of communication, and quotidian life in its interdisciplinary method with sociology as well. Therefore, this investigation was made possible through the phenomenon of computer-mediated interactions. This research followed three distinct methods of investigation in order to provide an overview; a) It presents the fake profiles as a subjective representation anonymous; b) The Web-novel is presented as an expression of such interactions mediated by the computer, and c) Everyday life as a sweeping of social phenomena in postmodernism. As a result of these approaches, all of the methods of investigation were distributed throughout the four chapters of this dissertation. The methodological approach was done through socialization and symbolic interactionism. Maffesoli‟s comprehensive sociology helps one to understand the relationships between the fake profiles, and its interpretation of the interactions with the profiles in the context of such virtual community according to Goffman. As one may noticed, the empirical study of the fake profile and its methodological feature investigated how interactions mediated by computer arose in daily life, and also how these interactions could be interpreted, and what were their impact on society. Thus, the analysis was done in two distinct moments. In the first one, five fake profiles were interviewed, and the authors of this web-novel within their community in order to analyze how they would interpret the interaction processes in the context of their community "Web-novels fake." In a second instant, five "key ideas" were categorized, and accordingly such data were collected accordingly to observation of the interaction between the readers profile and the author profile as well in a web-novel, which is already in progress. Such a web novel is called the Rented Boyfriend". In conclusion, it is obvious that there is an attempt to escape reality, or even a need for attention for oneself. One may also presuppose the young people who belong to this anonymous group to be likely to make a scapegoat of it. As a result of this analysis, one must observe such interactions as a new type of conversational approach of those whose fake can talk, construct ideas, stimulate dialogue, and promote discussions as well.